The Benefits of Windbreaks for Florida Growers - Michael G. Andreu; Bijay Tamang; Melissa H. Friedman; Donald L. Rockwood (EDIS)
FOR-192, a 5-page illustrated fact sheet by Michael G. Andreu, Bijay Tamang, Melissa H. Friedman, and Don Rockwood, focuses on the advantages and disadvantages of living windbreaks for improving crop production and enhancing conservation activities in sustainable agriculture systems. Includes references. Published by the UF School of Forest Resources and Conservation, July 2008.